Accuracy of Prenatal Diagnosis of Congenital Cardiac Malformations - Diesa Oliveira Pinheiro; Bruna Boff Varisco; Marcelo Brandão da Silva; Rafaela Silva Duarte; Graciele Dequi Deliberali; Carlos Roberto Maia; Mirela Foresti Jiménez; Patrícia El Beitune
Abstract Objective To evaluate the accuracy of the diagnosis of fetal heart diseases obtained through ultrasound examinations performed during the prenatal period compared with the postnatal evaluation. Methods A retrospective cohort study with 96 pregnant women who were attended at the Echocardiography Service and whose deliveries occurred at the Complexo Hospitalar Santa Casa de Porto Alegre, in the state of Rio Grande do Sul, Brazil. Risk factor assessment plus sensitivity and specificity analysis were used, comparing the accuracy of the screening for congenital heart disease by means of obstetrical ultrasound and morphological evaluation and fetal echocardiography, considering p < 0.05 as significant. The present study was approved by the Research Ethics Committee of the Institution. Results The analysis of risk factors shows that 31.3% of the fetuses with congenital heart disease could be identified by anamnesis. The antepartum echocardiography demonstrated a sensitivity of 97.7%, a specificity of 88.9%, and accuracy of 93% in the diagnosis of congenital heart disease. A sensitivity of 29.3% was found for the obstetric ultrasound, of 54.3% for themorphological ultrasound, and of 97.7% for the fetal echocardiography. The fetal echocardiography detected fetal heart disease in 67.7% of the cases, the morphological ultrasound in 16.7%, and the obstetric ultrasound in 11.5% of the cases. Conclusion There is a high proportion of congenital heart disease in pregnancies with no risk factors for this outcome. Faced with the disappointing results of obstetric ultrasound for the detection of congenital heart diseases and the current unfeasibility of universal screening of congenital heart diseases through fetal echocardiography, the importance of the fetal morphological ultrasound and its performance by qualified professionals is reinforced for a more appropriate management of these pregnancies.